Software Ecosystems
DOI: 10.4337/9781781955635.00014
|View full text |Cite
|
Sign up to set email alerts
|

The challenge of heterogeneously-licensed systems in open architecture software ecosystems

Abstract: =^Åèìáëáíáçå=oÉëÉ~êÅÜ=mêçÖê~ã= do^ar^qb=p`elli=lc=_rpfkbpp=C=mr_if`=mlif`v= 1= k^s^i=mlpqdo^ar^qb=p`elli= Approved for public release, distribution unlimited. Thomas Alspaugh-Thomas Alspaugh is adjunct professor of computer science at GeorgetownUniversity and visiting researcher at the Institute for Software Research at UC Irvine. His research interests are in software engineering and software requirements. Before completing his PhD, he worked as a software developer, team lead, and manager in industry and as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0
2

Publication Types

Select...
3
1
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(17 citation statements)
references
References 13 publications
0
15
0
2
Order By: Relevance
“…The ability to model and automatically analyze such obligations and rights is needed at build-time and release deployment-time. Automated analysis mechanisms then allow us to determine whether the specified component interconnections entail matches or conflicts in component-component license alignments [1,2]. However, we have also observed that design-time actions must accommodate build-time and deployment-time element bindings, as well as accommodate the evolution of licenses, policies, and system element versions [29].…”
Section: Architectural Design Processmentioning
confidence: 99%
See 4 more Smart Citations
“…The ability to model and automatically analyze such obligations and rights is needed at build-time and release deployment-time. Automated analysis mechanisms then allow us to determine whether the specified component interconnections entail matches or conflicts in component-component license alignments [1,2]. However, we have also observed that design-time actions must accommodate build-time and deployment-time element bindings, as well as accommodate the evolution of licenses, policies, and system element versions [29].…”
Section: Architectural Design Processmentioning
confidence: 99%
“…An OA system can evolve by a number of distinct mechanisms or process enactment pathways, some of which are common to all systems, but others of which arise only in OA systems or where components in a single system are heterogeneously licensed [2]. Figure 5 provides a summary of some of the various paths, further explained below.…”
Section: Evolution Processmentioning
confidence: 99%
See 3 more Smart Citations